TRANSMISSION-CONSTRAINED GENERATION EXPANSION PLANNING FOR A REAL-WORLD POWER INDUSTRY - Ananthan, Bhuvanesh (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
Transmission-constrained generation expansion planning (TC-GEP) problem for new generating units significantly involves location, capacity and type of fuel. This problem can be solved by adding Optimal Power Flow (OPF) constraints. This study renders an application of the Self-adaptive Differential Evolution (SaDE) algorithm to the TC-GEP problem for multiple horizons, at least cost, for the power generating system of Tamil Nadu, India. TC-GEP problem has been solved for 6-year (till 2022) and 12-year (till 2028) planning horizon by considering the least cost and reliable supply. The problem is solved for six different scenarios on an Indian utility 62 bus test system, and the results are validated with Dynamic Programming (DP). The results of the TC-GEP problem for the year 2028 are compared with the solutions of the GEP problem without transmission constraint. Finally, a comparison is made between the proposed solution and the practically implemented expansion plan for the year 2017 by the Tamil Nadu electricity sector.